Influence of Bypass Fat Supplementation on Productive Performance and Economics of Lactating Cows - Singh, Sunil; Singh, A K; Gautam, U S; Singh, Archana; Tiwari, D K; Sahay, Ratna (Indian Journal of Extension Education, 2020)
The present experiment was conducted on 20 healthy lactating cows of nearly similar age and stage of lactation to study Bypass fat supplementation on Productive Performance and Economics in lactating cattle in Unnao district. Cows were divided into 2 groups (10 cows in each group), which T1 was fed through farmers practices (control) (Use of concentrate, wheat straw and fodder) and T2 group in addition to farmers practices was supplemented with Bypass fat (20 g/day milk yield for 60 days and Fenbendazole 3 gm tablet used orally as dewormer at once). The results revealed that the milk yield and fat percent was significantly higher (P